Association between maternal decision-making and mental health and the nutritional status of children under 6 years of age in sub-urban Nigeria - Morenike Oluwatoyin Folayan; Ayodeji Babatunde Oginni; Maha El Tantawi; Abiola Adeniyi; Michael Alade; Tracy L Finlayson (BMC, 2023)
Abstract Background We assessed the association between decision-making power and mental health status of mothers and the nutritional status of their children less than 6 years old in Ile-Ife, Nigeria. Methods This was a secondary data analysis of 1549 mother-child dyads collected through a household survey conducted between December 2019 and January 2020. The independent variables were maternal decision-making and mental health status (general anxiety, depressive symptoms, parental stress). The dependent variable was the child's nutritional status (thinness, stunting, underweight and overweight). Confounders were maternal income, age, and education status, and the child's age and sex. The associations between the dependent and independent variables were determined using multivariable binary logistic regression analysis after adjusting for confounders. The adjusted odds ratios (AORs) were determined. Results Children of mothers with mild general anxiety had lower odds of stunting than children of mothers with normal anxiety (AOR: 0.72; p = 0.034). Mothers who did not make decisions on children's access to health care (AOR: 0.65; p < 0.001) had children with lower odds of being thin than those whose mothers made decisions on their access to health care. Children of mothers with clinically significant parenting stress levels (AOR: 0.75; p = 0.033), severe depressive symptoms (AOR: 0.70; p = 0.041) and who were not decision makers on the access of their children to health care (AOR: 0.79; p = 0.035) had lower odds of underweight. Conclusions Maternal decision-making status and mental health status were associated with the nutritional status of children less than 6 years in a sub-urban community in Nigeria. Further studies are needed to understand how maternal mental health is associated with the nutritional status of Nigerian preschool children.